Hands-On Machine Learning with IBM Watson Leverage IBM Watson to implement machine learning techniques and algorithms using Python - D. Miller, James (Packt Publishing Limited, 2019)
bLearn how to build complete machine learning systems with IBM Cloud and Watson Machine learning services/b h4Key Features/h4 ulliImplement data science and machine learning techniques to draw insights from real-world data /li liUnderstand what IBM Cloud platform can help you to implement cognitive insights within applications /li liUnderstand the role of data representation and feature extraction in any machine learning system/li/ul h4Book Description/h4 IBM Cloud is a collection of cloud computing services for data analytics using machine learning and artificial intelligence (AI). This book is a complete guide to help you become well versed with machine learning on the IBM Cloud using Python. Hands-On Machine Learning with IBM Watson starts with supervised and unsupervised machine learning concepts, in addition to providing you with an overview of IBM Cloud and Watson Machine Learning.